2019
DOI: 10.3389/fonc.2019.00465
|View full text |Cite
|
Sign up to set email alerts
|

Is Repeat Transurethral Resection Always Needed in High-Grade T1 Bladder Cancer?

Abstract: Re-staging transurethral resection, the so-called repeat TUR (Re-TUR), is mandatory in case of incomplete first transurethral resection of bladder tumor (TURBT). In completely resected high grade T1 tumors, Re-TUR is recommended but question remains whether it provides advantages in terms of recurrence-free survival (RFS), progression-free survival (PFS), and cancer specific survival (CSS). The present study aimed to determine whether Re-TUR improves such outcomes in patients with completely resected high-grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…presence of healthy detrusor muscle in the first TURBT specimen) high-grade (HG) T1 BC treated with intravesical BCG, Re-TUR did not improve RFS, PFS, and CSS [3]. Similar findings were obtained in a recent study addressing this issue in a homogeneous population of patients with completely resected HG T1 BC treated with intravesical BCG [4], thus questioning the dogmatic need for such additional surgical procedure, given its patients and healthcare burdens.…”
Section: Introductionsupporting
confidence: 64%
“…presence of healthy detrusor muscle in the first TURBT specimen) high-grade (HG) T1 BC treated with intravesical BCG, Re-TUR did not improve RFS, PFS, and CSS [3]. Similar findings were obtained in a recent study addressing this issue in a homogeneous population of patients with completely resected HG T1 BC treated with intravesical BCG [4], thus questioning the dogmatic need for such additional surgical procedure, given its patients and healthcare burdens.…”
Section: Introductionsupporting
confidence: 64%
“…They reported that the oncological results and the rate of recurrence / progression will not be affected after re-TUR for T1_high-grade. Moreover, re-TUR can cause patient distress and higher re-operation related healthcare costs 21 . In our study, we could not find any statically significant relation between re-TUR and recurrence/progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although second-look TUR-BT has been recommended for patients with stage pT1 BT after initial operation for re-staging and deciding the subsequent therapy. Some scholars queried the need for such additional surgical intervention, considering the patients and healthcare burdens, and the survival benefits of second-look TUR-BT is still controversial at present [ 12 , 16 ]. Hence, the majority of patients with stage pT1 bladder UC were not performed re-TUR-BT in our institution.…”
Section: Discussionmentioning
confidence: 99%